SEROEPIDEMIOLOGICAL STUDY OF CRIMEAN-CONGO HEMORRHAGIC FEVER (CCHF) IN WASIT GOVERNORATE, IRAQ 2024 - HUSAIN, THOLFIQAR (Archives of Veterinary Science, 2025)
Crimean-Congo hemorrhagic fever (CCHF) is a serious disease which lead to severe symptoms in humans with high mortality rate. The fact that Crimean-Congo hemorrhagic fever is asymptomatic in animals poses a danger. In last few years, there was an increase in the incidence of the (CCHF) in humans in Iraq. Current study conducted in the Wasit governorate in the middle of Iraq, making it the first in this region to address Crimean-Congo hemorrhagic fever. The study includes an investigation into the presence of antibodies for the Crimean Congo hemorrhagic fever virus (CCHFV) in sheep and goats using the (CCHF Double Antigen Multi-Species-CCHFDA ELISA KIT) To recognize the existence of IgG antibodies against the (CCHFV), as well as their correlation with the species, age, and sex of the animals. 196 samples of serum were collected from private farms and distributed in different areas of Wasit Governorate., which included 104 sheep and 92 goats. The results showed an overall seroprevalence rate of 37.2%, 35.6% in sheep, and 39.1% in goat. This indicates a serious warning and a likelihood of a rapid increase to spread to other areas, which directly impacts public health. Therefore, we recommend conducting further studies to investigate this disease more comprehensively, which will enhance our understanding of its nature and aid in developing programs to limit and control its spread.